VARIANCE OF BIOLOGICAL PROPERTIES OF OPPORTUNISTIC STAPHYLOCOCCUS UNDER NEGATIVE AERO IONS INFLUENCE - T. D. Primak; E. A. Shevchuk; S. L. Melnikova (Acta Biomedica Scientifica, 2012)
The aim. of this research was to study some changes of staphylococcus biological properties under negative aero ions influence and lactobacillus. We applied a disco-diffuse method for detection of bacterial sensitivity to antimicrobials and. evaluated of the minimal inhibitory concentration by bacteriologic analyzer. Then we studied impact of negative aeroions flow on both isolated staphylococcus culture and. mixed with lactobacilli. Aeroions flow inhibits staphylococcal growth, decrease its sensitivity to antibiotics in vitro both in isolated culture, and. mixed with lactobacilli. Combined application of probiotics and. negative aeroions could be a new approach for changes of antimicrobial sensitivity.